An Evaluation on Employment of Asylum Seekers in Turkey in terms of Human Capital - Ayguler, Edip; Ayalp, Mustafa Cagri; Yetkin-Aker, Deniz; Buz, Sema (Sosyoekonomi Soc, 2021)
In this study, the recruitment process for asylum seekers and their position within the Turkish job market is discussed in terms of human capital. The aim of this study is to identify the obstacles that asylum seekers encounter in employment and to offer suggestions that could facilitate the employment of asylum seekers in Turkey. A growing number of asylum seekers in Turkey cannot legally participate in employment due to various barriers; those who can participate usually work informally and under risky conditions. This, in turn, leads to a human capital loss through the deterioration of asylum seekers' current knowledge and skills. Therefore, opportunities should be facilitated for asylum seekers' to work in jobs that more suitably match their educational background, occupational knowledge and experience. Moreover, unskilled asylum seekers should be provided with technical and occupational education in order to enhance their human capital. Lastly, language education stands as an essential requirement in unlocking any human capital potential of asylum seekers in general.
Türkiye’deki Sığınmacı İstihdamının Beşerî Sermaye Açısından Değerlendirilmesi
Keywords: Asylum-Seekers in Turkey; Human Capital; Employment; Employment of Asylum-Seekers